The PACS-2 protein and trafficking motifs in CCHFV Gn and Gc cytoplasmic domains govern CCHFV assembly - Anupriya Gautam; Alexandre Lalande; Maureen Ritter; Natalia Freitas; Solène Lerolle; Lola Canus; Fouzia Amirache; Vincent Lotteau; Vincent Legros; François-Loïc Cosset; Cyrille Mathieu; Bertrand Boson (Emerging Microbes and Infections)
The Crimean-Congo hemorrhagic fever virus (CCHFV) is a tick-borne bunyavirus that causes high mortality in humans. This enveloped virus harbors two surface glycoproteins (GP), Gn and Gc, that are released by processing of a glycoprotein precursor complex whose maturation takes place in the ER and is completed through the secretion pathway. Here, we characterized the trafficking network exploited by CCHFV GPs during viral assembly, envelopment, and/or egress. We identified membrane trafficking motifs in the cytoplasmic domains (CD) of CCHFV GPs and addressed how they impact these late stages of the viral life cycle using infection and biochemical assays, and confocal microscopy in virus-producing cells. We found that several of the identified CD motifs modulate GP transport through the retrograde trafficking network, impacting envelopment and secretion of infectious particles. Finally, we identified PACS-2 as a crucial host factor contributing to CCHFV GPs trafficking required for assembly and release of viral particles.